Pengembangan Bisnis dan Tata Kelola Keuangan melalui Pendampingan UMKM Desa Serang Baru - Yahya, Adibah; Wulandari, Anna; Mulyanto, Heru; Kamela, Hurian; Permana, Adam Dede (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
The mentoring activities for business development and financial governance of MSMEs in Serang Baru Village aim to increase the capacity of business actors in managing their businesses effectively. Through training covering financial management, business planning, and technology utilisation, participants are expected to understand the importance of financial records and business development strategies. Monitoring and evaluation results showed a significant improvement in the understanding and skills of MSME players, which was reflected in better financial management and increased competitiveness of local products. Participants were able to record financial transactions more accurately and manage cash flow, thereby monitoring the financial health of their businesses. This activity is expected to contribute to business sustainability and local economic growth in Serang Baru Village and encourage MSME players to continue to innovate and improve the quality of their products.